Simulator and scale model of an industrial manufacturing cell - Mário de Sousa (2009)
As with most disciplines, the best way to learn and understand the relevant theoretical aspects related to industrial automation is by applying them to solve concrete problems. In order to increase the motivation of students a physical model of a manufacturing cell was acquired, which is, however, easily susceptible to being damaged through incorrect control sequences. To allow students safe access to this physical model, an interlocking application was designed and implemented. Additionally, a configurable software based simulator was also devised, which allows the students to work away from the laboratory in their own time. These tools have resulted in a higher flexibility in organizing courses and class work, due to their configurability and the way the physical model was integrated into the laboratory.